Analisis Kemampuan Pemecahan Masalah Matematis Siswa Ditinjau dari Perbedaan Gender - Shofia Hidayah; Moh. Farizal; Ma’rifatus Sholiha; Ahmad Khotibul Umam Khairi (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
Students need to have mathematical problem-solving skills to solve mathematical problems both in school and in real life. But in reality, students' mathematical problem-solving skills are still low. This study aims to analyze students' mathematical solving abilities from the perspective of gender differences, so that teachers can find the right solutions to improve students' abilities. This research is a qualitative research. The instruments used in this study are test questions and interview guidelines. The subjects of this study were three students taken from 20 students in grade VIII MTs Azzainiyah II. The subject consists of one student representing each of the high, medium, and low abilities. The results of the study showed that the mathematical solving ability of female students was better than that of male students. In the group of high-ability students, female students can meet all four indicators of the mathematical problem-solving stage, while male students can only meet the three indicators of the mathematical problem-solving stage. In the group of moderate-ability students, female students can meet three indicators of the mathematical problem-solving stage, while male students can only meet two indicators of the mathematical problem-solving stage. In the group of low-ability students, female students can meet two indicators of the mathematical problem-solving stage, while male students can only meet one indicator of the mathematical problem-solving stage.